Does Memory Accessibility Affect How Much We Learn from Studying? - Nate Kornell (Behavioral Sciences)
Two experiments were used to test the hypothesis that studying has a greater impact on learning when the information being studied is currently less accessible in memory. This hypothesis aligns with well-established findings like the spacing effect, but it is inconsistent with other evidence. Prior research has not directly tested the causal relationship between accessibility and learning. Two experiments were used to manipulate memory accessibility using semantic priming. The results indicated that differences in accessibility had no impact on learning. Retrieval difficulty and retrieval success also failed to influence learning. It is speculated that changes in accessibility that are specifically due to forgetting, rather than changes in accessibility per se, may have a causal impact on learning efficiency.